The Commodification of Childhood: Simulacra in The Boss Baby (2017) - Ayu Kusuma Septiani; Zalifa Nuri (Journal of Language and Literature, 2025)
One of the consequences of postmodernity is characterized by the rapid increase in materialistic needs. Materialism fuels the production and consumption of commodities, often exploited through marketing and advertising. The film The Boss Baby later became one of the films that discussed the theme of commodity in its narrative as it tries to present the simulated reality that commodifies childhood experience, depicted through the film. This study aims to examine the commodification of childhood and how Baudrillard's simulacra theory explains this phenomenon. This research is a qualitative study focusing on the phenomenon of commodification of childhood using the film The Boss Baby as the main subject for analysis. The results of this study show that the meaning of commodification found in The Boss Baby film is that it depicts how childhood is being commodified through Baby Corp., baby formula, parental love and affection, and toys. The analysis of Baudrillard's thoughts on simulacra in The Boss Baby film and commodification shows a match between the phenomenon that exists in the reality of a postmodern society depicted in The Boss Baby film, describing the simulated reality where babies are produced and managed as if they were products. It shows how modern society commodifies human life, relationships, and values.